Association of Mehran risk score and contrast-induced nephropathy in patients undergoing primary PCI - Adnan, Tanvir; Malik, Fazila Tun Nesa; Kalimuddin; Ahmed, Nazir; Ahmed, Mir Nesaruddin; Akhter, Ireen; Islam, Sami Nazrul; Hasan, Kamrul; Latif, Sayem Bin (International Journal of Research in Medical Sciences, 2026)
Background: Contrast-induced nephropathy (CIN) remains a common and serious complication following primary percutaneous coronary intervention (PCI) in patients with ST-elevation myocardial infarction (STEMI). Early risk stratification is essential to identify high-risk patients. The Mehran CIN risk score is widely used in elective PCI, but evidence in the primary PCI setting is limited. This study aimed to evaluate the association between Mehran risk score and the development of CIN in STEMI patients undergoing primary PCI. Methods: This cross-sectional analytical study was conducted in the department of cardiology, National Heart Foundation Hospital and Research Institute, Dhaka, from January 2018 to July 2019. Consecutive STEMI patients undergoing primary PCI were enrolled using a non-randomized purposive sampling method. Results: Among the study population, 34 (13.7%) patients developed CIN, while 214 (86.3%) did not. CIN occurred most frequently in higher Mehran risk categories, with a statistically significant association (p<0.05). Factors such as anemia, diabetes mellitus, baseline serum creatinine >1.5 mg/dl, eGFR <60 ml/minute/1.73 m2, and age >75 years were significantly associated with CIN. The ROC analysis showed an area under the curve of 0.774 (95% CI: 0.692-0.855; p<0.001). A Mehran score of 8 demonstrated 70% sensitivity and 71% specificity, while a score of 9 showed 61% sensitivity and 78% specificity. Conclusions: The Mehran CIN risk score is a useful and reliable tool for predicting contrast-induced nephropathy in STEMI patients undergoing primary PCI and may aid in early risk stratification and preventive strategies.